Enhancing Junior High School Students' Oral Communication Skills Through Media Learning - Ramadhanti, Erina Widya; Santoso, Dian Rahma (Inquest Journal, 2024)
This qualitative descriptive research investigates the learning media employed by English teachers for eighth-grade students at SMPN 1 Ngoro, Mojokerto. Utilizing observation and in-depth interviews, data were collected from teachers and students. Findings reveal two primary instructional media types: video and film recordings (YouTube) and printed media images. The study suggests that video and film recordings significantly influence student engagement, whereas printed media images appear less effective due to perceived lack of attractiveness. This study underscores the importance of selecting effective learning media, particularly in enhancing speaking skills development, offering valuable insights for English language educators